Photoluminescence of Silicon Nanocrystals in Silicon Oxide. (17th December 2007) - Ferraioli, L.; Wang, M.; Pucker, G.; Navarro-Urrios, D.; Daldosso, N.; Kompocholis, C.; Pavesi, L.
Abstract : Recent results on the photoluminescence properties of silicon nanocrystals embedded in silicon oxide are reviewed and discussed. The attention is focused on Si nanocrystals produced by high-temperature annealing of silicon rich oxide layers deposited by plasma-enhanced chemical vapor deposition. The influence of deposition parameters and layer thickness is analyzed in detail. The nanocrystal size can be roughly controlled by means of Si content and annealing temperature and time. Unfortunately, a technique for independently fine tuning the emission efficiency and the size is still lacking; thus, only middle size nanocrystals have high emission efficiency. Interestingly, the layer thickness affects the nucleation and growth kinetics so changing the luminescence efficiency.